Effects and associated transcriptomic landscape changes of methamphetamine on immune cells - Deshenyue Kong; Jun-Hong Mao; Hong Li; Jian-Yu Wang; Yu-Yang Li; Xiao-Cong Wu; Guo-Fen Re; Hua-You Luo; Yi-Qun Kuang; Kun-Hua Wang (BMC, 2022)
Abstract Background Methamphetamine (METH) abuse causes serious health problems, including injury to the immune system, leading to increased incidence of infections and even making withdrawal more difficult. Of course, immune cells, an important part of the immune system, are also injured in methamphetamine abuse. However, due to different research models and the lack of bioinformatics, the mechanism of METH injury to immune cells has not been clarified. Methods We examined the response of three common immune cell lines, namely Jurkat, NK-92 and THP-1 cell lines, to methamphetamine by cell viability and apoptosis assay in vitro, and examined their response patterns at the mRNA level by RNA-sequencing. Differential expression analysis of two conditions (control and METH treatment) in three types of immune cells was performed using the DESeq2 R package (1.20.0). And some of the differentially expressed genes were verified by qPCR. We performed Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analysis of differentially expressed genes by the clusterProfiler R package (3.14.3). And gene enrichment analysis was also performed using MetaScape ( www.metascape.org ). Results The viability of the three immune cells was differentially affected by methamphetamine, and the rate of NK-cell apoptosis was significantly increased. At the mRNA level, we found disorders of cholesterol metabolism in Jurkat cells, activation of ERK1 and ERK2 cascade in NK-92 cells, and disruption of calcium transport channels in THP-1 cells. In addition, all three cells showed changes in the phospholipid metabolic process. Conclusions The results suggest that both innate and adaptive immune cells are affected by METH abuse, and there may be commonalities between different immune cells at the transcriptome level. These results provide new insights into the potential effects by which METH injures the immune cells.